Do fã consumidor ao fã navegador-autor : o fenômeno fanfiction - Vargas, Maria Lucia Bandeira (2005)
The present study combines both bibliographic and field research aiming to introduce the fanfiction phenomena to the academic community, as well as propose some interpretation regarding its nature and the possible motivation behind its participants dedication to it. The field research consisted on sending, by e-mail, a questionnaire to be answered by fanfiction authors and then collecting their responses. The data collected was then studied in the light of the theory previously presented. The word fanfiction designates a fictional story, written having a previously existing one as its basis, by a fan of that original. In the research here presented it is understood as a spontaneous literacy practice, carried out mainly by young people who are in schooling age, as part of their leisure time activities, through which they establish for themselves the identity of authors